2007
DOI: 10.1016/j.immuni.2007.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Murine NK Cell Cytotoxicity Requires the Translation of a Pre-existing Pool of Granzyme B and Perforin mRNAs

Abstract: Although activated murine NK cells can use the granule exocytosis pathway to kill target cells immediately upon recognition, resting murine NK cells are minimally cytotoxic for unknown reasons. Here, we showed that resting NK cells contained abundant granzyme A, but little granzyme B or perforin; in contrast, the mRNAs for all three genes were abundant. Cytokine-induced in vitro activation of NK cells resulted in potent cytotoxicity associated with a dramatic increase in granzyme B and perforin, but only minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
411
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 397 publications
(446 citation statements)
references
References 61 publications
32
411
3
Order By: Relevance
“…To date, this heterogeneity has not been examined at the protein level for murine virus-specific CTL. Independent grz regulation is observed for resting murine NK cells that contain abundant grzA protein but little grzB [22]. Our analysis demonstrated that grzA was expressed only together with grzB in all of the virus-specific CTL populations examined.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…To date, this heterogeneity has not been examined at the protein level for murine virus-specific CTL. Independent grz regulation is observed for resting murine NK cells that contain abundant grzA protein but little grzB [22]. Our analysis demonstrated that grzA was expressed only together with grzB in all of the virus-specific CTL populations examined.…”
Section: Discussionmentioning
confidence: 57%
“…1A). The CD8 À grzA 1 population is presumably NK cells [22]. Interestingly, CD8 1 grzA 1 CTL were always a subset of CD8 1 grzB 1 influenza A virus-specific CTL (Fig.…”
Section: Detection Of Grza Expression By Ctl Following Influenza a VImentioning
confidence: 86%
See 1 more Smart Citation
“…Altogether, these results suggest the possibility that iNKT might regulate, at least to some extent, their cytokine secretion through such a translational mechanism. Whether it might apply to all cytokines/chemokines that are produced by iNKT cells and perhaps to their cytotoxic apparatus [36], remains to be determined.…”
Section: Cytokine and Chemokine Productionmentioning
confidence: 99%
“…Type I interferons and cytokines that bind to the common γ-chain-containing receptors, such as IL-2 and IL-15, enhance NK cell responses. In mice, circulating NK cells do not express abundant perforin and granzyme B, until cytokine stimulation induces translation of pre-existing mRNA [80]. Recent experiments have suggested that such priming is delivered by contact with dendritic cells and trans-presentation of IL-15 [81*].…”
Section: Dynamic Tuning Of Nk Cell Effector Responsesmentioning
confidence: 99%